Sinau: Javanese Educational Games for Early Childhood as an Effort to Preserve Javanese Heritage - Pratama, Nanda Zakir Shihab; Ratnasari, Chanifah Indah (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Preserving the Javanese language is a collective responsibility to safeguard Indonesia's cultural heritage. This study aims to develop Sinau, a Javanese language learning game for early childhood (ages 4–8), focusing on vocabulary and unggah-ungguh (Kromo and Ngoko) with correct pronunciation. Utilizing the Game Development Life Cycle (GDLC) and Guided Discovery methods, the game was designed to facilitate active learning both at home and school. GDLC encompassed pre-production (concept, teaching methods, and prototype development), production (game creation with Unity, incorporating educational content, visuals, and sound), and post-production phases. Testing involved 10 second-grade students and 2 teachers, with observations despite the game's primary target being younger children. Participants evaluated the game by playing it and completing a 10-question Likert-scale questionnaire. Usability was measured using the System Usability Scale (SUS), resulting in a score of 74.17, indicating an acceptable level with a good adjective rating. These results demonstrate that Sinau is well-received and effective for Javanese language learning. While the study did not directly test early childhood learning outcomes, the findings suggest the game's potential for educational use, with recommendations for improving user experience and content to enhance its effectiveness further.